Research of Kinematics Calibration Model for the Reptiles- like Quadruped Robot - Yang Xu; Pan Chunmei; Wang Liangwen; Song Kangkang (Jixie chuandong)
Aiming at motion error problems of walking robot in the actual movement,a geometric parameter model of the robot is established based on introducing structure of reptiles- like robot Mini Quad- Ⅰ. The relationships among the robot parameters error and the structure size and the trajectory error are discussed,the kinematics calibration model of this kind of robot is studied in detail. By measuring the change of the body posture and each joint movement angle,the structure parameters of the robot are calibrated,when the robot movements in given trajectory. The automatic calculation system for parameters calibration is developed,and parameters calibration process is illustrated with example. A foundation for establishing relatively accurate control models of the robot is laid by the research.